Dystopian Humour and Postcolonial Anomie in Femi Osofisan’s Midnight Hotel - Ogunrotimi, Olumide (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This article explores the intersection of humour and postcolonial themes in Femi Osofisan’s Midnight Hotel through the lens of postcolonial contextualisation. Osofisan, a prominent Nigerian playwright, employs satire and dark humour to depict a dystopian society grappling with the protracted ramifications of colonialism. The play is the author’s satirical condemnation of Nigeria’s debased value system, as he deconstructs a wasteland of underdevelopment, corruption, and amorality. The aim of the paper is to analyse how Osofisan critiques power structures, societal norms, and the failures of postcolonial governance through humour. Central to this analysis is the concept of "postcolonial anomie," referring to the moral and social disorientation experienced in societies transitioning from colonial rule to independence. Utilising a close textual analysis of the play’s major elements, the research methodology involves examining how Osofisan employs humour to depict and critique the dystopian reality of postcolonial Nigeria. The findings reveal that Osofisan’s portrayal of postcolonial anomie through humour adds complexity to the narrative, highlighting both the absurdity and tragedy of the characters’ predicaments. Moreover, the article uncovers how Osofisan incorporates dystopian elements to underscore the consequences of unchecked power and corruption, offering a cautionary tale about the dangers of authoritarianism and neocolonialism. By blending satire with poignant social commentary, Midnight Hotel emerges as a powerful vehicle for critiquing contemporary issues within the postcolonial context. In conclusion, this article contributes to the understanding of Osofisan’s literary legacy and the role of humour in interrogating complex sociopolitical dynamics in postcolonial societies.